Pore size effect on cell response via plasma electrolytic oxidation. (2nd June 2016) - Shin, K. R.; Kim, Y. S.; Jeong, J. H.; Ko, Y. G.; Shin, D. H.
Abstract : Using a plasma electrolytic oxidation (PEO) process, this study investigated how the pore size of the coating surface influences the growth of osteoblast cells and their morphology in pure titanium. With this aim, PEO coatings were applied using four different electric and electrolyte conditions to vary the mean pore sizes of the coatings from ∼2 to ∼5 μm. In vitro examinations showed that the osteoblast cells on the surface of the coating with ∼2 μm pores had grown healthily with good attachment by multiple pseudopodia connections; cells were highly proliferated, compared to those of other samples. In addition, the coating with ∼2 μm pores showed the highest cell viability among the samples.